Chemical Composition Of Female And Male Giant African Crickets, Brachytrypes Membranaceus L - E.I. ADEYEYE; E.E. AWOKUNMI (International Journal of Pharma and Bio Sciences, 2010)
Female and male dry samples of giant African crickets, Brachytrypes membranaceus L were analysed. The comparison of female and male results showed that significant differences (p<0.05) existed in the correlation coefficients in the proximate composition (rxy = 0.89), mineral composition (rxy = 0.79), amino acids composition ((rxy = 0.81), and amino acid scores (rxy = 0.84); with corresponding regression coefficients (Rc) of: proximate (0.74), minerals (0.62), amino acids (0.50) and amino acid scores (0.51). The above showed that the composition values in the female samples were higher than in the male samples in the various parameters determined.